Feature : What next for Fukushima?. (9th February 2018) - Drinkwater, Bruce; Malkin, Rob
Abstract: Nearly seven years after a powerful tsunami caused catastrophic damage to Japan's Fukushima Daiichi nuclear-power plant, the clean-up and recovery is still ongoing. Bruce Drinkwater and Rob Malkin recently visited the disaster site and the undamaged Tsuruga plant to see if they can pinpoint the true extent of the damage in the dangerously radioactive reactors